Efficacy of a Structured Psychoeducation Program in Enhancing Nomophobia Awareness: A Randomized Controlled Trial Among University Students in Kolkata - Shankar, Ravi; Kumar, Sunil; Bolotaolo, Alven M. (Journal of Educational Research and Policies, 2025)
Introduction: Nomo phobia, a growing behavioral addiction to mobile phones, poses significant challenges in today’s digital age. This study explores the effectiveness of psycho education on enhancing college students' knowledge of Nomo phobia in selected colleges in Kolkata. The study aimed to identify the baseline knowledge of college students regarding Nomo phobia in both experimental and control groups, assess the effect of psycho education on knowledge levels through pre-test and post-test comparisons, and evaluate the association between students' pretest knowledge scores and selected demographic variables. Methodology: Utilizing a quasi experimental design, the research employed a stratified random sampling technique to assign 120 undergraduate students (60 in the experimental group and 60 in the control group). Data were gathered using self-administered structured questionnaires. Knowledge scores were analyzed through descriptive and inferential statistics. Results: The findings indicated a significant increase in mean post- test knowledge scores among the students in experimental group, with a mean difference of 9.80 [t(59) = 24.74, p ≤ 0.05)]. A comparable significant difference in post-test knowledge scores was observed when comparing the experimental group to the control group (mean difference 9.82; [t (118) = 26.72, p ≤ 0.05)]. Furthermore, demographic variables such as age, living conditions, monthly family income, duration of mobile phone usage, and daily time spent on mobile phones showed no statistically significant association with pre-test knowledge scores. Conclusion: The study underscores the effectiveness of psycho education in improving knowledge about Nomo phobia among college students. It highlights essential implications for nursing practice, education, administration, and further research in the field of behavioral addictions.